RANCANG BANGUN SISTEM PAKAR PENYAKIT TANAMAN CABAI MENGGUNAKAN METODE NAÏVE BAYES BERBASIS WEB - Khairunnas Khairunnas; Husna Gemasih; Hendri Syahputra (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
In this study a web-based expert system was designed using the Naïve bayes method which was intended to help farmers diagnose chili plants. The system development method used is extreme programming which consists of planning, design, coding, testing. A web-based chilli plant disease diagnostic expert system was developed using the PHP and MySQL programming languages. This expert system is capable of diagnosing chili plants by submitting disease symptoms at the time of inspection. Based on the selected symptoms, this system will provide diagnostic results and then display the disease and solutions for the chili plant disease. The results in this study concluded that there was compatibility between the results of the expert system diagnosis using the Naïve bayes method with experts.